Floración primera del zacate gigante del Volcán Turrialba, Costa Rica - Pohl, Richard W. (Revista de Biología Tropical, 1973)
A giant grass growing stwms up to 6 m tall and forming a large colony in a swamp on the SW slope of Volcán Turrialba. Costa Rica, has never been seen to bloom by the local inhabitants, nor by the author since 1966, neither has it responded to various photoperiods in cultivation at the Department of Botany and Plant Pathology of Iowa State University. Spontaneous flowering of one of these plants confirmed a previous determination on anatomic characters as Phragmites australis (Cav.) Trin. ex Steud.